A systematic review and meta-analysis on “Adjacent Segment Impingement Due to Long Rods in Spine Surgery (Bangladesh Journal of Neurosurgery, 2026)
Long-segment spinal fusion using long rods is commonly employed to treat various spinal pathologies,  including deformities and degenerative diseases. However, adjacent segment impingement (ASI) and adjacent  segment degeneration (ASD) remain critical complications. This systematic review and meta-analysis is  assessed to examine the impact of long rods on adjacent segment biomechanics, the incidence of ASI/ASD,  and clinical outcomes.  Methods:  A systematic analysis was conducted in PubMed, Embase, Web of Science, and Cochrane Library for articles  published until February 2025. Studies investigating adjacent segment changes in patients undergoing  long-rod spinal fusion were included. Data were extracted on clinical outcomes, radiographic ASD, symptomatic  ASI, revision rates, and risk factors. Meta-analysis was performed using RevMan 5.4 software.  Results:  A total of 23 studies (n = 5,764 patients) met the inclusion criteria. The pooled incidence of radiographic ASD  was 31.2% (95% CI: 27.1–35.6%), while symptomatic ASI occurred in 9.4% (95% CI: 6.7–12.5%) of patients.  Patients with long-segment fusion (≥5 levels) had a significantly higher risk of ASI compared to those with  shorter constructs (OR: 2.87, 95% CI: 2.01–4.13, P < 0.001). Biomechanical studies indicated increased  motion and stress at the adjacent segments in long-rod constructs. Risk factors included advanced age,  excessive segmental distraction, and sagittal imbalance.  Conclusions:  Long rods used in spinal fusion surgery significantly elevate the risk of adjacent segment impingement and  degeneration. Although these constructs offer improved stability, their mechanical stress on adjacent levels  significantly results in higher revision rates when the rods impinge on the facet joints. Future strategies should  focus on dynamic stabilization techniques, hybrid constructs, and improved surgical planning to mitigate ASI  risks.Bang. J Neurosurgery 2025; 14(2):  142-147